The myth of the misinformed migrant? Survey insights from Nigeria's irregular migration epicenter - Bernd Beber; Alexandra Scacco (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022)
Policy projections and recent research suggest that large numbers of irregular migrants from sub-Saharan Africa will continue to attempt to make their way to Europe over the next few decades. In response, European countries have made and continue to make significant investments in information campaigns designed to discourage irregular African migration. Despite the ubiquity of these campaigns, we know relatively little about potential migrants' prior knowledge and beliefs. To what extent are potential migrants actually misinformed about the migration journey and destination countries? We bring representative survey data collected in Benin City, Nigeria - a center of irregular migration - to bear on this question. Three key insights emerge. First, potential migrants are better informed about destination contexts than is commonly assumed, and if anything appear to underestimate the economic benefits of life in Europe. Second, they are relatively less well informed about specific risks and other features of the irregular migration journey. Third, we find evidence of optimism bias. Respondents are generally hopeful when asked about Nigerian irregular migrants' prospects of being able to reach and stay in Europe, but they are especially optimistic when asked about their own chances. Taken together, these findings suggest that existing migration-related information campaigns, and with them a central component of migration policies in countries across the Global North, rest on shaky foundations. Most problematically, our study suggests that campaigns risk becoming misinformation campaigns, particularly when they suggest to potential migrants that they are overestimating the benefits of living in Europe. – – Politische Prognosen und Forschungsergebnisse deuten darauf hin, dass auch in kommenden Jahrzehnten eine bedeutende Zahl irregulärer Migranten aus Subsahara-Afrika versuchen wird, nach Europa zu ziehen. Als Reaktion darauf haben europäische Länder umfangreich in Informationskampagnen investiert, um irreguläre Migration zu unterbinden. Allerdings wissen wir nur wenig über das Vorwissen und die Überzeugungen potenzieller Migranten. Inwieweit sind potenzielle Migranten tatsächlich falsch informiert? Wir bringen repräsentative Umfragedaten aus Benin City, Nigeria - einem Zentrum irregulärer Migration - in diese Frage ein. Es ergeben sich drei wichtige Erkenntnisse. Erstens sind potenzielle Migranten besser über Zielländer informiert, als gemeinhin angenommen wird, und scheinen die wirtschaftlichen Vorteile eines Lebens in Europa zu unterschätzen. Zweitens sind sie verhältnismäßig weniger gut über spezifische Risiken und andere Merkmale der irregulären Migrationsreise informiert. Drittens finden wir Hinweise auf eine optimistische Einstellung. Die Befragten sind im Allgemeinen hoffnungsvoll, wenn sie nach den Aussichten nigerianischer irregulärer Migranten, Europa zu erreichen und dort bleiben zu können, gefragt werden, aber sie sind besonders optimistisch, wenn sie nach ihren eigenen persönlichen Chancen gefragt werden. Zusammengenommen stellen diese Ergebnisse Aspekte bestehender migrationsbezogener Informationskampagnen und damit eines zentralen Bestandteils der Migrationspolitik des Globalen Nordens in Frage. Besonders problematisch ist, dass manche Kampagnen Gefahr laufen, zu Fehlinformationskampagnen zu werden.
Keywords: F22; O15; D83; D91; 330; Migration; information campaigns; beliefs; Nigeria